Blocked Pipes: The Economic Consequence of Skilled Worker Shortages - Dunham, John; Flaherty, Michael (Journal of Applied Business and Economics, 2024)
The thinning of the supply of skilled labor is having major negative implications on the economy. This research explores the “skilled labor gap” by examining the plumbing industry and quantifying the economic value lost through inefficiencies and labor premiums. The analysis utilizes state-level panel data for the years 2010 to 2018, employing both a linear OLS model of pooled data and a random effects regression model to determine the relationship between the number of plumbers and the price of plumbing services (proxied in plumber wages). Price effects are modeled across industries to determine the effects on the overall economy.